Preservation approaches for high-traffic-volume roadways - Peshkin, David G. (Transportation Research Board, 2011)
TRB's second Strategic Highway Research Program (SHRP 2) Report S2-R26-RR-1: Preservation Approaches for High-Traffic-Volume Roadways documents the state of the practice of preservation treatment on asphalt and concrete pavements on high- and low-volume roadways. The report also includes general guidelines on the application of preservation treatments on high-volume roadways. The same project that produced SHRP 2 Report S2-R26-RR-1 also produced SHRP 2 Report S2-R26-RR-2: Guidelines for the Preservation of High-Traffic-Volume Roadways, which explores the state of the practice for preservation treatments on high- and low-volume asphalt and concrete roadways. The report also includes suggested guidelines on the application of preservation treatments on high-volume roadways.
At head of title: The Second Strategic Highway Research Program.
Keywords: Pavements -- United States -- Maintenance and repair.; Roads -- United States -- Maintenance and repair.; United States.; elektronické knihy; electronic books